Digital Capitalism and Platform Dependency in Indonesia: Media, Power, and Political Economy - Widodo, Suko; Kristiyono, Jokhanan; Aji, Gilang Gusti; Zulaikha, Zulaikha (Universitas Negeri Surabaya, 2026)
This article examines Indonesia’s digital transformation through a political economy of media perspective, focusing on platform dependency, digital labor, and governance relations. The study employs a qualitative analysis of secondary data, including national statistics, policy documents, industry reports, and recent academic studies related to Indonesia’s digital economy and media systems. Drawing on sources such as APJII (2023), BPS (2023), and regional digital economy reports, the analysis captures large-scale patterns of platform adoption, labor dynamics, and governance structures. The findings indicate that Indonesia’s digital ecosystem is characterized by structural asymmetries in infrastructural control, value extraction, and regulatory capacity. Rather than reflecting technological progress alone, digital transformation involves a reconfiguration of media power and platform-mediated participation. This article contributes to media and communication scholarship by offering an integrated political economy framework to understand how digital capitalism reshapes communication environments in emerging digital societies